Exercise-induced oxidative stress: Friend or foe? - Scott K. Powers; Rafael Deminice; Mustafa Ozdemir; Toshinori Yoshihara; Matthew P. Bomkamp; Hayden Hyatt (Elsevier, 2020)
The first report demonstrating that prolonged endurance exercise promotes oxidative stress in humans was published more than 4 decades ago. Since this discovery, many ensuing investigations have corroborated the fact that muscular exercise increases the production of reactive oxygen species (ROS) and results in oxidative stress in numerous tissues including blood and skeletal muscles. Although several tissues may contribute to exercise-induced ROS production, it is predicted that muscular contractions stimulate ROS production in active muscle fibers and that skeletal muscle is a primary source of ROS production during exercise. This contraction-induced ROS generation is associated with (1) oxidant damage in several tissues (e.g., increased protein oxidation and lipid peroxidation), (2) accelerated muscle fatigue, and (3) activation of biochemical signaling pathways that contribute to exercise-induced adaptation in the contracting muscle fibers. While our understanding of exercise and oxidative stress has advanced rapidly during the last decades, questions remain about whether exercise-induced increases in ROS production are beneficial or harmful to health. This review addresses this issue by discussing the site(s) of oxidant production during exercise and detailing the health consequences of exercise-induced ROS production.